The pH-Responsive Transcription Factor PacC Governs Pathogenicity and Ochratoxin A Biosynthesis in Aspergillus carbonarius - Barda, Omer; Maor, Uriel; Sadhasivam, Sudharsan; Bi, Yang; Zakin, Varda; Prusky, Dov; Sionov, Edward (Frontiers in Microbiology, 2020)
Pathogenic fungi must respond effectively to changes in environmental pH for successful host colonization, virulence and toxin production. Aspergillus carbonarius is a mycotoxigenic pathogen with the ability to colonize many plant hosts and secrete ochratoxin A (OTA). In this study, we characterized the functions and addressed the role of PacC-mediated pH signaling in A. carbonarius pathogenicity using designed pacC gene knockout mutant. ΔAcpacC mutant displayed an acidity-mimicking phenotype, which resulted in impaired fungal growth at neutral/alkaline pH, accompanied by reduced sporulation and conidial germination compared to the wild type (WT) strain. The ΔAcpacC mutant was unable to efficiently acidify the growth media as a direct result of diminished gluconic and citric acid production. Furthermore, loss of AcpacC resulted in a complete inhibition of OTA production at pH 7.0. Additionally, ΔAcpacC mutant exhibited attenuated virulence compared to the WT towards grapes and nectarine fruits. Reintroduction of pacC gene into ΔAcpacC mutant restored the WT phenotype. Our results demonstrate important roles of PacC of A. carbonarius in OTA biosynthesis and in pathogenicity by controlling transcription of genes important for fungal secondary metabolism and infection.